2013
DOI: 10.3324/haematol.2013.086959
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor produces long-term changes in gene and microRNA expression profiles in CD34+ cells from healthy donors

Abstract: © F e r r a t a S t o r t i F o u n d a t i o ngene and miRNA expression profiles in HPC from healthy donors, and to determine whether any changes in expression signatures persist in the long-term or return to the original status. Methods SamplesCD34 + progenitor cells from peripheral blood of six healthy donors were collected before and at 5, 30 and 365 days after the mobilization with G-CSF (mobilization regimen: 10-15 mg/kg of G-CSF daily for 5 days). All donors were included in the transplant program of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…We have not performed any functional assays to evaluate the potential association between metabolites altered by G-CSF and immunomodulatory effects; however, G-CSF has been shown to induce several cellular and immunological changes in donor cells (Anderlini et al 1996; Shaw et al 2015), and several of the altered metabolites found in our study have known immunoregulatory and/or angioregulatory effects, or can be markers of altered regulation of epigenetic/gene expression that may contribute to the previously described long-lasting effects after G-CSF therapy (Baez et al 2014). Altered metabolite levels may reflect the direct effects of G-CSF on different immune cell types, affecting cell proliferation, differentiation and function, but also indirect effects through e.g.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We have not performed any functional assays to evaluate the potential association between metabolites altered by G-CSF and immunomodulatory effects; however, G-CSF has been shown to induce several cellular and immunological changes in donor cells (Anderlini et al 1996; Shaw et al 2015), and several of the altered metabolites found in our study have known immunoregulatory and/or angioregulatory effects, or can be markers of altered regulation of epigenetic/gene expression that may contribute to the previously described long-lasting effects after G-CSF therapy (Baez et al 2014). Altered metabolite levels may reflect the direct effects of G-CSF on different immune cell types, affecting cell proliferation, differentiation and function, but also indirect effects through e.g.…”
Section: Discussionmentioning
confidence: 53%
“…Changes in global gene expression profiles were then described both at early time points after G-CSF administration (up to 5 days) (Hernandez et al 2005) and after 2–10 months (Amariglio et al 2007), and even a year after G-CSF administration in CD34 + progenitor cells (Baez et al 2014). These studies have revealed that there seems to be both early responses to G-CSF, transient changes that are normalized over time and more long-lasting changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not all studies can be directly compared with each other due to differences in the cellular population, time points at testing, or testing methodology, the majority have shown only transient abnormalities in either chromosomal number (or other abnormalities) or gene expression profiles. The exception is a study by Baez et al, 31 which does show persistent changes at 1 year post exposure. Further analyses of this sort are warranted to investigate the significance of these findings and correlation with the clinical condition for these donors is necessary.…”
Section: Summary and Updated Statementmentioning
confidence: 92%
“…30 A few recent studies have addressed the issues of whether these changes in donor cells are persistent invivo. Baez et al 31 examined isolated CD34+ cells from six healthy donors before G-CSF exposure and on day 5, 30 and 365 after G-CSF mobilisation. They found that changes in both gene expression profiles and miRNAs were present and persisted until at least 1 year after the administration of G-CSF.…”
Section: Changes In Gene Expression Profilesmentioning
confidence: 99%